Gender Differences of NLRP1 Inflammasome in Mouse Model of Alzheimer's Disease - Jinghang Zhang; Jinghang Zhang; Lihong Pei; Dan Zang; Yun Xue; Xiaohui Wang; Yiyang Chen; Jinsong Li; Jian Yu; Qingzu Gao; Wenyu Di; Chaochu Cui; et al. (Frontiers in Aging Neuroscience, 2020)
Background: There is a significant gender difference in the incidence and symptoms of Alzheimer's disease (AD), but its mechanisms are not completely understood. Recent studies showed that NLRP1 inflammasome was overexpressed in females under some pathological conditions such as nodular melanoma. Whether NLRP1 signals have a gender difference in AD has not been elucidated. This study was designed to investigate gender difference on the expressions of NLRP1 signals including NLRP1, Capase-1 and IL-1β in the brains of APP/PS1+/− mice.Methods: Female and male APP/PS1+/− mice (30-weeks-old) were used in this study. Amyloid-β (Aβ) plaques were stained with Congo red dye and cell apoptosis was detected by TUNEL staining. Expressions of NLRP1, Capase-1 and IL-1β were measured by immunofluorescent staining and Western blotting assay.Results: The numbers of Aβ plaques in cortex and hippocampus and neuronal apoptosis in cortex were 4 and 2-folds in females than males, respectively (P < 0.001). The average size of Aβ plaques in both cortex (females: 3527.11 ± 539.88 μm2 vs. males: 1920.44 ± 638.49 μm2) and hippocampus (females: 1931 ± 308.61 μm2 vs. males: 1038.55 ± 220.40 μm2) were also larger in females than males (P < 0.01). More interestingly, expressions of NLRP1, Caspase-1, and IL-1β were markedly increased in the cortex of females as compared with males.Conclusions: These findings show that NLRP1 signals are higher in brains of female APP/PS1+/− mice than males, which may be related to the gender differences of AD.